1996
DOI: 10.3133/ofr96559
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for estimating monthly mean streamflow at gaged sites and monthly streamflow duration characteristics at ungaged sites in central Nevada

Abstract: Techniques for estimating monthly mean Streamflow at gaged sites and monthly Streamflow duration characteristics at ungaged sites in central Nevada were developed using Streamflow records at six gaged sites and basin physical and climatic characteristics. Streamflow data at gaged sites were related by regression techniques to concurrent flows at nearby gaging stations so that monthly mean streamflows for periods of missing or no record can be estimated for gaged sites in central Nevada. The standard error of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…For the specific monthly relations, the R 2 ranged from 0.10 to 0.94 (average 0.72), and the SEE ranged from 36 to 237 percent (average 78 percent; table 6). The accuracy of both types of regression equations developed in this study generally is comparable to those in the previous study by Hess and Bohman (1996). This study had a slight increase in SEE probably because of a wetter period of record (1995)(1996)(1997)(1998)(1999)(2000) used and a wider range in streamflow values.…”
Section: Methods For Estimating Monthly Streamflow-duration Charactersupporting
confidence: 83%
See 4 more Smart Citations
“…For the specific monthly relations, the R 2 ranged from 0.10 to 0.94 (average 0.72), and the SEE ranged from 36 to 237 percent (average 78 percent; table 6). The accuracy of both types of regression equations developed in this study generally is comparable to those in the previous study by Hess and Bohman (1996). This study had a slight increase in SEE probably because of a wetter period of record (1995)(1996)(1997)(1998)(1999)(2000) used and a wider range in streamflow values.…”
Section: Methods For Estimating Monthly Streamflow-duration Charactersupporting
confidence: 83%
“…Averages not available in Parrett and Cartier. In the study area, Hess and Bohman (1996) reported that for all months the R 2 for equations ranged from 0.73 to 0.92 (average 0.85) and the SEE ranged from 51 to 96 percent (average 69 percent); and for specific months the R 2 for equations ranged from 0.33 to 0.97 (average 0.83) and the SEE ranged from 31 to 168 percent (average 74 percent).…”
Section: Methods For Estimating Monthly Streamflow-duration Charactermentioning
confidence: 90%
See 3 more Smart Citations